The possibilities of non-formal education in MOOCs - Zaduski, Jeong Cir Deborah (2017)
This paper covers the possibilities of learning in a non-formal environment named Unesp Aberta, in courses offered in a MOOC format, in an open, free and accessible virtual space, without tutoring or certification where the construction of knowledge is possible and witnessed from the interaction between students. To verify the effectiveness of this hypothesis, the research was divided into three studies. The first was to know the profile of participants in this environment, identifying who they are and what are their needs. The second was to ascertain the degree of satisfaction of students regarding the course, the proposed materials, the existing interactions and their perception about the learning obtained. The third was to identify mechanisms of communication and interaction between apprentices, based on discussion forums and other means. Methodological approach adopted was quantitative and qualitative, using two instruments: the non-participant observation of three discussion forums and a semi-structured questionnaire sent to all participants of the Human Sciences courses. The 675 questionnaires considered valid were quantitatively analyzed and, the postings made in the discussion forums and the answers given in the open question of the questionnaire, were analyzed qualitatively with the help of the Iramuteq software. The study provided the identification of the learners’ profile, the understanding of their perceptions regarding educational resources available and, regarding the general structure. In addition, it was possible to affirm that were found evidence of learning in the non-formal education environment analyzed.